Uncommon dominion : Venetian Crete and the myth of ethnic purity - McKee, Sally (Middle Ages series., 2000)
"Uncommon Dominion tells the story of Venetian Crete, the home of two recognizably distinct ethnic communities, the Latins and the Greeks. The Greeks were subordinate to the Latins economically, politically, and juridically, yet within a century of Venetian colonization, the ethnic differences between Latin and Greek creations in daily material life were significantly blurred." "Members of the groups intermarried, many of them learned each other's language, and some even chose to worship by the rites of the other's church. Holding up ample evidence of acculturation and miscegenation by the colony's inhabitants, McKee uncovers the colonial forces that promoted the persistence of ethnic labeling despite the lack of any clear demarcation between the two predominant communities. As McKee argues, the concept of ethnic identity was largely determined by gender, religion, and social status, especially by the Latin and Greek elite in their complex and frequently antagonistic social relationships." "Drawing expertly from notarial and court records, as well as legislative and literary sources, Uncommon Dominion offers a unique study of ethnicity in the medieval and early modern periods. Students and scholars in medieval, colonial, and postcolonial studies will find much of use in studying this remarkable colonial experiment."--Jacket.